Evaluation of AODV and DSR Performance Using Jellyfish Delay Variance Attack with Self-Cooperative Trust Scheme - Deepika (My University, 2018)
In applications with low infrastructural elements, a MANET becomes highly vulnerable to security attacks. These attacks can be active or passive in nature. Active attacker including ‘Black-hole’, ‘Grey-hole’ and ‘Worm-hole’; can modify, listen and inject messages in communication channel. Whereas, a passive attacker does not alter the information; but secretly listens to valuable information i.e. spoofing. Jellyfish attack is one of the illustrations of a passive attack. Jellyfish conforms to all routing and forwarding protocol specifications. A Jellyfish attacker possesses the property that it is difficult to detect until after the sting. Jellyfish attacker targets closed loops and misguide the packets to adversely affect the network performance. A Jellyfish attack can attack the network in 3-ways Jellyfish-reorder-attack, Jellyfish-periodic-dropping-attack and Jellyfish-delay-variance-attack. In Jellyfish Delay Variance (JFDV) attack, attacker node receives the packets from source side and adds delay while forwarding the packets to receiver. This leads to automatic performance degradation in both sender and receiver perspective. JFDV attack causes delayed ACK and sender assumes that packet has been lost and begins to retransmit the packet leading to congestion in the network. Routing protocols specifies the ways to establish the route from source to destination. The established route belongs to reactive and proactive category. AODV and DSR fall under the category of reactive routing protocol or on demand routing protocol. The AODV routing protocol is based on DSDV and DSR. In AODV, each packet carries the destination path, whereas in DSR each packet carries full routing information. Moreover AODV is adaptive to highly dynamic network. The present work has been implemented on network simulator, NS 2.35. It is a discrete set of terms and protocol settings for network lay-outing and configurations. The present work has taken 2-routing protocols AODV and DSR; on which JFDV attack has been implemented. The impact of varying number of jellyfish attacker nodes 1, 3, 6 and 9 has been compared in both the protocols. AODV outperforms DSR protocol for several performance parameters, which include “Throughput” and “End to End Delay” with JFDV detection algorithm. The Algorithm provides better identification and removal in AODV protocol.
Keywords: AODV, DSR, Jellyfish Attack